(untitled) (Journal of Engineering, 2021)
In this paper, numerical and experimental studies on the elastic behavior of glass fiber reinforced ‎polymer (GFRP) with stiffeners in the GFRP section’s web (to prevent local buckling) are presented. ‎The GFRP profiles‎ were connected to the concrete deck slab by shear connectors. Two full-scale simply supported ‎composite beams (with and without stiffeners) were tested under impact load (three-point load) to ‎assess its structural response. The results ‎proved that the maximum impact force, maximum ‎deflection, damping time, and ‎damping ratio of the composite beam were affected by the GFRP ‎stiffeners‎. The experimental results indicated that the damping ratio and deflection were diminished compared to hybrid beam without stiffeners by ‎‎16% and 22%, respectively, and increasing damping time‏ by 26%. Finite element models were used to study pre-failure behavior. ‎ The numerical modeling results showed good agreement with experimental data in terms of loading path and ‎final load. The damping ratio and midspan deflection values were greater than the experimental ‎values by 6% and 12%, respectively.